Breastfeeding and breast cancer: a case-control study in patients at Arzobispo Loayza National Hospital. Lima - Peru - Rojas Camayo, José (2008)
Introduction: Breast cancer is a global public health problem with incidence increasing in the world. Breastfeeding has been shown to be a protective factor, but evaluation in Latin American populations has scant. Objective: To evaluate the effect of breastfeeding on breast cancer developing risk in a Peruvian population. Design: A case-control study. Setting: Departments of Medical Oncology and Radiology, section of Mammography, at Arzobispo Loayza National Hospital, Lima - Peru. Participants: Patients with breast cancer and women with Birads 1 and 2 mammograms. Interventions: Information was collected from July 2006 through October 2007 from 103 patients with breast cancer as cases and 208 women with Birads 1 and 2 mammograms as controls. Interviews included information on risk factors and patterns of breastfeeding. We used descriptive statistics, and bivariate and logistic regression analysis. Main outcome measures: Breastfeeding protection on breast cancer. Results: Absence of breastfeeding was associated with a non- significant risk increase compared with patients that ever lactated (adjusted OR 1,99; 95% CI 0,23-6,99). Excluding nulliparous, women that breastfed one month or more per child had a non-significant reduced risk compared with women that breastfed less than a month per child (adjusted OR 0,28, 95% CI 0,06-1,27). However, women who breastfed 3 months or more had a significant reduction in breast cancer risk compared with those that never breastfed or breastfed less than 3 months (adjusted OR 0,24; 95% CI 0,06-0,92). Conclusions: Breastfeeding by parous women showed protection on breast cancer risk especially if breastfeeding period was for three month or more.